Tuning adhesion forces between functionalized gold colloidal nanoparticles and silicon AFM tips: Role of ligands and capillary forces - Sven Oras; Sergei Vlassov; Marta Berholts; Rünno Lõhmus; Karine Mougin (Beilstein-Institut Zur Forderung der Chemischen Wissenschaften, 2022)
Adhesion forces between functionalized gold colloidal nanoparticles (Au NPs) and scanning probe microscope silicon tips were experimentally investigated by atomic force microscopy (AFM) equipped with PeakForce QNM (Quantitative Nanoscale Mechanics) module. Au NPs were synthesized by a seed-mediated process and then functionalized with thiols containing different functional groups: amino, hydroxy, methoxy, carboxy, methyl, and thiol. Adhesion measurements showed strong differences between NPs and silicon tip depending on the nature of the tail functional group. The dependence of the adhesion on ligand density for different thiols with identical functional tail-group was also demonstrated. The calculated contribution of the van der Waals (vdW) forces between particles was in good agreement with experimentally measured adhesive values. In addition, the adhesion forces were evaluated between flat Au films functionalized with the same molecular components and silicon tips to exclude the effect of particle shape on the adhesion values. Although adhesion values on flat substrates were higher than on their nanoparticle counterparts, the dependance on functional groups remained the same.